Resisting neoliberal policies in UK higher education: Exploring the impact of critical pedagogies on non-traditional students in a post-1992 university. (November 2018) - Sanders-McDonagh, Erin; Davis, Carole
In this article, we focus on how neoliberal performance metrics impact on non-traditional students at a modern university in England. We argue that the introduction of 'quality assurance' measures, (such as the National Student Survey and the Teaching Excellence Framework) are driven by an ideology which purports to have student's best interests at heart by raising teaching standards, focusing on graduate employability and wider participation, but in fact works to discourage critical pedagogic practices that would allow for more democratic and dialogic spaces of learning. This article presents findings from one multi-modal qualitative case study at a particular higher education institution in London, where many of the students originate from socially and economically deprived areas and frequently come from ethnic minority groups. We argue that the radical space of the classroom provides a unique opportunity for students to move into collective and empathetic modes of learning that yield both normative measures of 'success' as well as more transformative outcomes. We maintain that critical pedagogies work to disrupt the neoliberal narrative that champions individual success and the student-as-consumer model, and by doing so, helps to redress the persistent inequalities that non-traditional students face in UK higher education settings.